Effects of Salt Soaking Treatment on the Deodorization of Beef Liver and the Flavor Formation of Beef Liver Steak - Yufeng Duan; Ziqi Liu; Dan Deng; Li Zhang; Qunli Yu; Guoyuan Ma; Xiaotong Ma; Zhaobin Guo; Cheng Chen; Long He (Foods, 2023)
In this study, based on the evaluation of fishy value and sensory evaluation, this study determined that soaking in a 1% salt solution for 60 min had a significant impact on the deodorization of beef liver (p < 0.05). The results showed that salt infiltration promoted the release of fishy substances, improving the edible and processing performance of beef liver. The identification of flavor compounds in raw and roasted beef liver via GC–IMS implies that (E)–2–octenal–M, (E)–3–penten–2–one–M, ethyl acetate–M, ethyl acetate–D, and methanethiol are closely related to improving the flavor of beef liver; among them, (E)–2–octenal–M, (E)–3–penten–2–one–M, and methanethiol can cause beef liver odor, while nonanal–M, octanal–M, benzene acetaldehyde, n–hexanol–D, butyl propanoate–M, heptanal–D, heptanal–M, and 3–methylthiopropanal–M had significant effects on the flavor formation of beef liver steak. The determination of reducing sugars revealed that salt soaking had no significant effect on the reducing sugar content of beef liver, and the beef liver steak was significantly reduced (p < 0.05), proving that reducing sugars promoted the formation of beef liver steak flavor under roasting conditions. Fatty acid determination revealed that salt soaking significantly reduced the content of polyunsaturated fatty acids in beef liver (p < 0.05), promoting the process of fat degradation and volatile flavor production in the beef liver steak. Salt plays a prominent role in salting–out and osmosis during deodorization and flavor improvement. Through controlling important biochemical and enzymatic reactions, the release of flavor substances in a food matrix was increased, and a good deodorization effect was achieved, which lays a foundation for further research on the deodorization of beef liver and the flavor of beef liver steak.